The fall of the Assad regime: Regional and international power shifts - Sinem Adar; Muriel Asseburg; Hamidreza Azizi; Margarete Klein; Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2025)
On 8 December 2024, the Assad regime in Syria was overthrown by a rebel alliance led by Hay'at Tahrir al-Sham (HTS). The collapse of the family dictatorship was made possible by shifts in regional and international power dynamics. Key factors included Turkish support for the rebels, the weakening of Iran and Hezbollah owing to Israeli military strikes and Russia's changing priorities in the context of its war against Ukraine. At the same time, the fall of the Assad regime has led to another shift in power relations in the region. The interests, priorities and actions of regional and international actors will define the room for manoeuvre of the new rulers in Damascus. Turkey and Israel have occupied territories in the north and southwest of the country, respectively. The Arab monarchies of the Persian Gulf are expected to exercise influence, too, as they will play a crucial role in the reconstruction of Syria. And the United States still maintains a military presence in Syria, although its future involvement in the country is uncertain.
Keywords: 320; Syria; Assad Regime; Bashar al-Assad; Hay'at Tahrir al-Sham (HTS); Islamic State (IS); balance of power; Turkey; Kurds; Iran; Hezbollah; Israel; Russia; war against Ukraine; Gulf Arab monarchies; United States; Syrian Democratic Forces (SDF); al-Qaeda; Nusra Front